Comparison of the tumor immune microenvironment phenotypes in different breast cancers after neoadjuvant therapy - Mengxue Han; Jinze Li; Si Wu; Chun Wu; Yongqiang Yu; Yueping Liu (Cancer Medicine)
Abstract Neoadjuvant therapy (NAT) treats early‐stage breast cancers, especially triple‐negative breast cancers (TNBCs). NAT improves pathological complete response (pCR) rates for different breast cancer patients. Recently, immune checkpoint inhibitors that target programmed death 1 (PD‐1) or programmed death ligand 1 (PD‐L1) in combination with NAT have shown antitumor activity in patients with early breast cancer. However, the tumor immune microenvironment (TME) in different subtypes of breast cancers, like TNBC, hormone receptor‐positive (HR+), and human epidermal growth factor receptor 2 amplified (HER2+) and its changes by NAT remain to be fully characterized. We analyzed pre‐NAT tumor biopsies from TNBC (n = 27), HR+ (n = 24), and HER2+ (n = 30) breast cancer patients who received NAT, followed by surgery. The different immune makers (PD‐1, PD‐L1, CD3, and CD8) of tumor‐infiltrating lymphocytes (TILs) were identified with immunofluorescence‐based microenvironment analysis. TILs within cancer parenchyma (iTILs) and in cancer stroma (sTILs) were counted separately. We found that PD‐L1+ cells in tumor and stroma were significantly higher in TNBC patients than in others. PD‐L1+ sTILs were significantly higher in pCR than in non‐pCR patients of all the subtypes. The infiltration scores of B‐cell memory, T‐cell CD4+ memory activated, T‐cell follicular helper, and Macrophage M0 and M1 were relatively higher in TNBC patients, indicating immunoreactive TME in TNBC. Analysis of TCGA‐BRCA RNA‐seq indicated that PD‐L1 was highly expressed in TNBC patients compared with HR+ and HER2+ patients. Higher PD‐L1 expression in TNBC patients was associated with significantly longer overall survival (OS). Our results demonstrated that PD‐L1 expression level of iTILs and sTILs is highest in TNBC among breast cancers. TNBC patients had significantly different immunoreactive TME compared with HR+ and HER2+ patients, suggesting potentially favorable outcomes for immunotherapy in these patients. Also, PD‐L1+ could be a powerful predictor of pCR in TNBC patients after NAT.